2012
DOI: 10.1159/000339583
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Porphyromonas gingivalis</i></b> Accelerates Neointimal Formation after Arterial Injury

Abstract: <b><i>Background:</i></b> Inflammation plays a key role in neointimal hyperplasia after an arterial injury. Chronic infectious disorders, such as periodontitis, are associated with an increased risk of cardiovascular diseases. However, the effects of a periodontal infection on vascular remodeling have not been examined. We assess the hypothesis that periodontal infection could promote neointimal formation after an arterial injury.<b><i> Methods:</i></b> Mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 90 publications
0
13
1
Order By: Relevance
“…36 We have shown that P. gingivalis infection increased the number of MCP-1 positive cells in the neointimal area in WT mice. 13 In this study, however, the P. gingivalis-infected TLR4KO mice significantly suppressed the number of MCP-1 positive cells in the neointimal area compared with the P. gingivalis-infected WT mice. TLR4 ligand stimulation induced MCP-1 production in murine macrophage-like cells.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…36 We have shown that P. gingivalis infection increased the number of MCP-1 positive cells in the neointimal area in WT mice. 13 In this study, however, the P. gingivalis-infected TLR4KO mice significantly suppressed the number of MCP-1 positive cells in the neointimal area compared with the P. gingivalis-infected WT mice. TLR4 ligand stimulation induced MCP-1 production in murine macrophage-like cells.…”
Section: Discussioncontrasting
confidence: 61%
“…22 Recently, we reported that P. gingivalis infection accelerated neointimal formation after arterial injury. 13 It has also been reported that Chlamydia pneumonia infection induced neointimal formation after arterial injury. 23 Inflammation after infection is now considered a factor that worsens cardiovascular disease.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We were focused on systemic inflammation in this study. The mouse subcutaneous chamber model is a model of local infection in a distant area, which was previously shown to mimic the sequence of localized inflammatory events observed in diseased human periodontal pockets (21,26). Moreover, it was said that assessment of host responses to localized infections can be performed quite easily with the use of subcutaneous chambers implanted in mice (16).…”
Section: Discussionmentioning
confidence: 99%
“…1) Recently, we demonstrated that P. gingivalis deteriorated AAA [8][9][10] and wire-injury induced arteriosclerosis 14) in animal models. Furthermore, we demonstrated that A. actinomycetemcomitans aggravated ventricular remodeling after myocardial ischemia 15) and pressure overload-induced myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%